How to Escape the Microfinance Lending Squeeze : Evidence from Ethiopia - Alibhai, Salman; Bessir, Mengistu; Weis, Toni (World Bank, Washington, DC, 2021)
Across the world, small-scale lenders - including microfinance institutions (MFIs), community-based financial institutions, and other nonbank financial institutions - have grappled with uncertainty through the Coronavirus disease 2019 (COVID-19) pandemic as portfolio quality deteriorated and capital buffers were drawn down. Ethiopia’s microfinance borrowers - particularly micro and small enterprises (MSEs) are currently facing a financing squeeze that undermines their resilience during the COVID-19 crisis and threatens to slow their recovery. Although Ethiopian MFIs entered the crisis in good financial health, they soon began to face deteriorating portfolios and a contraction in liquidity. Drawing on data collected from a panel of major MFIs, this policy brief provides an overview of the microfinance lending squeeze in Ethiopia and outlines ways to overcome it. Sections one and two looks at the impact of the COVID-19 pandemic on Ethiopian MFIs and on their borrowers, respectively, and show how MFIs responded to liquidity constraints by cutting off financing to MSEs. Sections three and four discuss possible ways out of the crisis, outlining four concrete ways to ease the squeeze and highlighting new interventions in Ethiopia that provide emergency financing to MFIs and the MSEs they serve. The aim of this brief is to shed light on the lending squeeze in Ethiopia, and to share lessons for post-pandemic microfinance lending globally.